Handbook of Philosophical Logic Volume 15 - Gabbay, Dov M.; Guenthner, Franz; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Lambda Calculi: A Guide Interpolation and Definability Discourse Representation Theory
Editorial Preface -- Dov M. Gabbay -- Lambda Calculi: A Guide -- Chris Hankin -- Interpolation and Definability -- Dov Gabbay and Larisa L. Maksimova -- Discourse Representation Theory -- Hans Kamp, Josef van Genabith and Uwe Reyle -- Index.
Keywords: Computer science; Computer vision; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Philosophy; Linguistics (general).